2010
DOI: 10.3732/ajb.0900215
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers show decreasing diversity but unchanged level of clonality inDryas octopetala(Rosaceae) with increasing latitude

Abstract: The newly developed microsatellite markers provide a useful tool for further genetic studies of D. octopetala and its close relatives, addressing population structure as well as phylogeographic patterns. The results of this study support the hypothesis of decreasing genetic diversity with increasing latitude, which may have implications for future adaptability to climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…We assessed the relationships between intrapopulation genetic diversity parameters, namely SSR‐based gene diversity ( H E ), SSR‐based allelic richness ( A R ), AFLP‐based genetic diversity, nucleotide diversity (π) of the cpDNA and LEAFY sequences and the SSR‐based inbreeding coefficient ( F ), and latitude using linear and quadratic regression models in which latitude was an explanatory variable (Guo, ; see Figure for details). In the analysis of SSR‐based gene diversity, we used data of 13 populations from Svalbard and Norway (from Vik et al., ), in addition to the original 18 populations, for which joint estimates based on eight SSRs (D3, D5, D8, D11, D13, D14, D17 and D21) were available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the relationships between intrapopulation genetic diversity parameters, namely SSR‐based gene diversity ( H E ), SSR‐based allelic richness ( A R ), AFLP‐based genetic diversity, nucleotide diversity (π) of the cpDNA and LEAFY sequences and the SSR‐based inbreeding coefficient ( F ), and latitude using linear and quadratic regression models in which latitude was an explanatory variable (Guo, ; see Figure for details). In the analysis of SSR‐based gene diversity, we used data of 13 populations from Svalbard and Norway (from Vik et al., ), in addition to the original 18 populations, for which joint estimates based on eight SSRs (D3, D5, D8, D11, D13, D14, D17 and D21) were available.…”
Section: Methodsmentioning
confidence: 99%
“…Skrede, Eidesen, Portela, and Brochmann () conducted a phylogeographical survey of D. octopetala across the Northern Hemisphere (42.1°N–79.9°N) and reported that in extant populations genetic diversity was higher in northern than in southern populations. In contrast, Vik, Jørgensen, Kauserud, Nordal, & Brysting () found that within‐population genetic diversity of D. octopetala decreases with increasing latitude in high‐latitude regions around the North Atlantic (59.0°N–79.9°N). One interpretation of these contradictory results is that at global scale intraspecific genetic diversity in this arctic–alpine species decreases towards the equator, whereas at regional scale, that is, around the northern margins of its range, diversity decreases polewards.…”
Section: Introductionmentioning
confidence: 95%
“…Six microsatellites successfully amplified and were used to analyse 10 individuals from each of the 12 Cochlearia populations from Northern Norway, following the protocol by Vik et al . 82 except that 10 μl PCR reaction volumes were used. The annealing temperature used for each microsatellite after optimisation is given in Supporting Information Table S6.…”
Section: Methodsmentioning
confidence: 99%
“…Some of them have focused on the genetic variability of the species, the possibility of crossing with D. integrifolia, its postglacial migration and possible refugia (Philipp and Siegismund 2003;Vik et al 2010). Skrede et al (2006), in her research on molecular differentiation of Dryas octopetala sensu lato within the whole circumpolar range found that the populations of the species Philipp and Siegismund (2003), who analyzed the hybrid zone between D. octopetala and D. integrifolia in Greenland.…”
Section: Introductionmentioning
confidence: 99%